The Double-Edged Sword of SIRT3 in Cancer and Its Therapeutic Applications - Ouyang, Shumin; Zhang, Qiyi; Lou, Linlin; Zhu, Kai; Li, Zeyu; Liu, Peiqing; Zhang, Xiaolei (Frontiers in Pharmacology, 2022)
Reprogramming of cellular energy metabolism is thought to be an emerging hallmark of cancer. Mitochondrial metabolism is essential for cancer proliferation, survival, and metastasis. As a major mitochondria NAD+-dependent deacetylase, SIRT3 deacetylates and mediates the enzymesinvolved in regulating mitochondrial energy metabolism, including fatty acid oxidation, the Krebs cycle, and the respiratory chain to maintain metabolic homeostasis and balance. In this article, we review the multiple roles of SIRT3 in various cancers, and systematically summarize the recent advances in the discovery of activators and inhibitors. The roles of SIRT3 vary in different cancers with cell and tumor-type specificity. SIRT3 plays a unique function by mediating cross-talking between mitochondrial regulation and intracellular signaling cascades. The critical functions of SIRT3 have aroused interest to develop small molecule modulators that regulate its activity. Delineation of the underlying mechanism of SIRT3 as a critical regulator of cell metabolism and further characterization of the mitochondrial substrates of SIRT3 will enhance our better understanding of the role of SIRT3 in tumorigenesis and progression. Thus, it will provide novel therapeutic strategies for cancer therapy by targeting SIRT3.